Biomechanical Comparison of Modified Adams-Berger and DX technique in DRUJ Reconstruction - Rigó, István Zoltán; Riano, Felix; Kalapos, Robert; Haugstvedt, Jan-Ragnar (Journal of Wrist Surgery, 2021)
Background Adams-Berger ligamentoplasty is a widely accepted reconstruction for unrepairable triangular fibrocartilage complex (TFCC) injuries with instability. Failure of the reconstruction and recurrent instability is still a clinical problem. Internal brace augmentation of tendon grafts is gaining more popularity, but use in the distal radioulnar joint (DRUJ) is not yet published.Questions/Purposes The purpose of this study was to compare a novel anatomical DRUJ reconstruction with a modified Adams-Berger reconstruction to answer which technique stabilize better the DRUJ and which has enough stabilizing effect to allow early mobilization.Methods Nine matched pairs of cadaveric upper extremities were used. The dorsopalmar translations in the DRUJ that occurred with 50 N load were measured before and after detachment of the TFCC from the ulna and after ligament reconstruction with either modified Adams-Berger procedure or DX Swivelock technique. Internal brace augmented palmaris longus tendon grafts were used in all reconstruction.Results In the Adams-Berger group, the injured and the reconstructed displacements were significantly higher than the native, while in the DX group both the native and the reconstructed displacements were significantly lower than the injured. The mean (standard deviation) change of translations was 0.46 (1.94) mm after Adams-Berger and 2.51 (1.31) mm after DX reconstruction, implying significant better stabilizing effect of the latter.Conclusions DX Swivelock reconstruction showed better time zero stabilizing effect compared with Adams-Berger procedure, regaining almost normal stability of the DRUJ.
Keywords: distal radioulnar joint; instability; ligament reconstruction